Elevated high-sensitivity C-reactive protein and dyslipidaemia in type 2 diabetes mellitus: implications for cardiovascular risk prediction in Nigerian patients - Jamila Aminu Mohammed; Bruno Basil; Izuchukwu Nnachi Mba; Nabilah Datti Abubakar; Akeem Oyeyemi Lawal; Jafaru Alunua Momoh; Isah Adagiri Yahaya (BMC Endocrine Disorders)
Abstract Background Cardiovascular disease (CVD) is a leading cause of morbidity and mortality among individuals with type 2 diabetes mellitus (T2DM). Inflammation, marked by elevated high-sensitivity C-reactive protein (hs-CRP) levels, and dyslipidaemia, are critical contributors to atherosclerosis and cardiovascular risk. In Nigeria, where T2DM prevalence is rising, there is a need for more comprehensive risk prediction tools, incorporating both traditional and newer biomarkers such as hs-CRP. This study aimed to investigate the association between elevated hs-CRP levels and dyslipidaemia in Nigerian patients with T2DM and to explore the potential implications for cardiovascular risk prediction. Methods A hospital-based cross-sectional study was conducted among 150 T2DM patients and 150 age-matched controls. Data on socio-demographics, medical history, clinical characteristics, and laboratory parameters, including lipid profiles and hs-CRP levels, were collected. The relationship between hs-CRP levels and lipid parameters was assessed using Pearson’s correlation coefficient and independent t-tests. Results T2DM patients exhibited significantly higher hs-CRP levels (2.2 ± 1.8 mg/L vs. 1.2 ± 1.0 mg/L, p < 0.001), dyslipidaemia (p < 0.001), and blood pressure (SPB– 127.6 ± 12.4 mmHg, DBP– 77.6 ± 6.6 mmHg vs. SBP– 119.6 ± 10.8 mmHg, DBP– 72.1 ± 8.0 mmHg; p = 0.001) compared to controls. However, no significant correlation was found between hs-CRP levels and lipid parameters. Conclusion Although no direct association was found between elevated hs-CRP levels and dyslipidaemia, hs-CRP remains an important marker of cardiovascular risk possibly through non-lipid pathways, such as inflammation-driven endothelial dysfunction. Further research is needed to evaluate its potential role in refining cardiovascular risk assessment in the Nigerian T2DM population. Clinical trial number Not applicable.